Ankle motor strategy use in older and younger adults as assessed by a two-dimensional kinematic analysis smart device application. (2nd October 2020) - Criminger, Christina; Thompson, Mary; Swank, Chad; Medley, Ann
Abstract : Background/aims: Motor strategies change with age, resulting in balance deficits. Clinical options for objectively measuring motor strategies are limited. The use of two-dimensional kinematic analysis through smart devices and applications may provide a cost-effective portable solution for measuring differences in motor strategy use between older and younger adults. The aims of this study were to investigate the concurrent validity of a two-dimensional software and two-dimensional application and to determine whether the application could capture the difference in ankle motor strategy use by older and younger adults (construct validity). Methods: Video clips captured by Sony and iPad Air cameras were used to assess concurrent validity between the two-dimensional software and application. A total of 30 older (72.6 ± 4.0 years) and 30 younger (26.5±4.5 years) adults performed forward and backward stepping. A two-dimensional applicationmeasured the ankle position in degrees and time taken in seconds to initiate and complete a compensatory step. Results: The two-dimensional software and app demonstrated excellent reliability (ICC2, 1 ≥0.994). The ankle forward stop angle differed significantly between older and younger adults ( P =0.012). No differences were observed in time taken to initiate and complete a compensatory step. Conclusions: The two-dimensional application appears to be a valid alternative to two-dimensional software for measuring ankle motor strategies. Further investigation for clinical use is warranted.